Bridging Economic Theory Models and the Cointegrated Vector Autoregressive Model - Niels Framroze Møller (Kiel Institute for the World Economy (IfW), 2008)
Examples of simple economic theory models are analyzed as restrictions on the Cointegrated VAR (CVAR). This establishes a correspondence between basic economic concepts and the econometric concepts of the CVAR: The economic relations correspond to cointegrating vectors and exogeneity in the economic model implies the econometric concept of strong exogeneity for â. The economic equilibrium corresponds to the so-called long-run value (Johansen 2005), the comparative statics are captured by the long-run impact matrix, C; and the exogenous variables are the common trends. Also, the adjustment parameters of the CVAR are shown to be interpretable in terms of expectations formation, market clearing, nominal rigidities, etc. The general-partial equilibrium distinction is also discussed.
Keywords: C32; 330; Cointegrated VAR; unit root approximation; economic theory models; expectations; general equilibrium; DSGE models; VAR-Modell; Kointegration; Wirtschaftsmodell; Allgemeines Gleichgewicht